Potensi Probiotik sebagai Agen Terapi Rhinitis Alergi Terbarukan: Literature Review pada Uji Klinis - Giska Tri Putri; Aloysius Krishartadi Damar Bawono; Gresia Rosi Chofifah; Nisrina Zalfa Fatin; Aulia Fifi Malika; Julian Mahendra; Faalih Mathul Hajariyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Allergic rhinitis is a chronic inflammatory disease that occurs widely in the global population. This disease is related to the body's hypersensitivity to allergens from the external environment. Available therapy for allergic rhinitis is only symptomatic, while primary therapy has several problems, such as access, time, and cost. Research related to renewable rhinitis therapy is needed, one of which is the use of probiotics as a therapeutic agent. The research method used was a literature review through the PubMed and GoogleScholar databases using the keywords